EVALUASI KINERJA APARAT DALAM PELAYANAN PEMBUATAN PENGANTAR E-KTP DI KELURAHAN MAMASA KECAMATAN MAMASA KABUPATEN MAMASA - Richard Richard; Rustan IR Rustan IR; M. Syariat Tajuddin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
This study aims to determine the performance evaluation of officers in the service of making e-KTP introductions in Mamasa Village, Mamasa District, Mamasa Regency. The research method used is descriptive research with a qualitative approach. The results showed that the performance of the Mamasa village apparatus was good but still needed to be improved in providing services to the community. In addition, the community expects the quality of public services to increase in the form of services that are fast, easy, fair, with legal certainty, transparent, safe, precise, free of charge, and accountable. In terms of the identity card service, the community wants a truly quality service.